Contextualizing Fatwas amid Social Change: A Maqasid-Based Comparative Framework of Legal Reasoning in MUI, Muhammadiyah, and Nahdlatul Ulama - Ilda Hayati; Busman Edyar; Desfitranita; Busahdiar; Juliansyah (AL-ISTINBATH : Jurnal Hukum Islam, 2026)
This study examines how Indonesian fatwa institutions contextualize Islamic legal rulings in response to social change through a maqasid-based framework of legal reasoning. While previous studies have explored the institutional authority, legal methodology, and implementation of fatwas in Indonesia, limited attention has been given to the comparative mechanisms through which the Indonesian Ulema Council (MUI), Muhammadiyah, and Nahdlatul Ulama (NU) reconcile textual authority with evolving social realities. This research employs normative juridical and library research methods using a usul al-fiqh approach. Primary data consist of fatwas issued by MUI, Muhammadiyah, and NU, complemented by relevant classical and contemporary literature. The data were analyzed using qualitative content analysis and comparative legal analysis. The findings demonstrate that the three institutions employ distinct yet complementary models of legal reasoning in contextualizing fatwas. MUI emphasizes collective ijtihad and public policy considerations, Muhammadiyah adopts a maqasid-oriented rational approach through bayani, qiyasi, and istislahi reasoning, while NU integrates the authority of classical legal tradition with a gradual methodological shift toward manhaji reasoning. Despite their methodological differences, all three institutions consistently prioritize the objectives of Islamic law, particularly the protection of religion, life, intellect, and public welfare, when responding to contemporary legal challenges. This study proposes a maqasid-based comparative framework that explains how different fatwa institutions maintain the authority of Islamic legal texts while adapting legal rulings to changing social contexts, thereby contributing to contemporary discussions on Islamic legal reasoning, fatwa studies, and maqasid al-shariah.